Multipoint left ventricular pacing provides additional echocardiographic benefit to responders and non-responders to conventional cardiac resynchronization therapy. (9th March 2015) - Pappone, Carlo; Ćalović, Žarko; Cuko, Amarild; McSpadden, Luke C.; Ryu, Kyungmoo; Jordan, Caroline D.; Saviano, Massimo; Baldi, Mario; Pappone, Alessia; Dozza, Luca; Giannelli, Luigi; Fragakis, Nikolaos; et al.
Abstract: Cardiac resynchronization therapy (CRT) with multipoint left ventricular (LV) pacing [MultiPoint™ Pacing (MPP), St. Jude Medical, Sylmar, CA, USA] improves LV function and clinical response relative to conventional CRT in patients receiving a de novo device implant. We hypothesized that patients with a previously implanted conventional CRT device would receive additional benefit by switching to MPP. Patients receiving a CRT implant (Unify Quadra MP™ or Quadra Assura MP™ CRT-D and Quartet™ LV lead, St. Jude Medical) were programmed to conventional CRT (i.e. biventricular pacing with right ventricular and single LV sites) optimized by intraoperative haemodynamic measurements. After 12 months of conventional therapy, patients were reprogrammed to MPP and re-evaluated at 16 months post-implant. Response to CRT was prospectively defined as reduction in end-systolic volume (ESV) of ≥15% relative to baseline as determined by a blinded observer. Eight patients with an implanted CRT device [New York Heart Association III, ejection fraction (EF) 30 ± 5%, QRS 149 ± 18 ms] received 12 months of conventional CRT and were switched to MPP. After 12 months of conventional CRT, ESV reduction and EF increase relative to baseline were −18 ± 12 and +5 ± 4%, respectively, and six of eight (75%) patients were considered CRT responders. After 4 months of MPP, two of two (100%) patients classified as non-responders to conventional CRT became responders with additional reduction in ESV of −33 and −20% and improvement in EF of +15 and +4%. The remaining six patients classified as responders experienced additional reduction in ESV of −13 ± 21% and improvement in EF of +7 ± 7% after switching to MPP. Multipoint LV pacing may provide additional improvement to LV function in patients receiving conventional CRT.